Technological-Productive Changes in Work: Ecuadorian Juridical Issues - Rodríguez-Mendoza, Carolina (2022)
The research objective has been to outline the relationships between technological and productive transformations in the work. To reach that, a qualitative methodology of documentary review and intuitive contribution was followed on the theoretical descriptive basis of concepts such as: technology, innovation, creation, social changes, productive transformations; and, mainly, employment within the framework of the concept of work. As it is a descriptive and exploratory level investigation; The relationships that have been found from the scientific literatu-re in this area of knowledge are delineated and the possible existence of more relationships is formulated. Finally, this study exposes the importance of technological change; look at the process of technological transformation in the social context, raises the emergency or need for a new paradigm; fixes the relationship between technology, technological innovation, social change and work to conclu-de on its dimensions, the type of relationship and its effects; It also highlights the difficulties, limits and challenges that this issue represents for the contemporary world, especially on employment from a legal perspective illustrated in problems of the current Ecuadorian context.